2020
DOI: 10.1111/jcms.12977
|View full text |Cite
|
Sign up to set email alerts
|

Collective Identities, European Solidarity: Identification Patterns and Preferences for European Social Insurance

Abstract: A degree of collective identity is often perceived to be a requirement for integration of core state powers, and even more so when redistributive measures are at stake. Existing research has shown that European identity is an important correlate of support for European social policy in general. This article explores the ways in which collective identities relate to the multidimensional nature of social policy at the European level. We explore in particular the features of European social policy that receive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The authors assess how collective identities impact on preferences for different designs of EU policy packages (for example, with varying redistribution potential, governance and conditionality). Building on the concepts presented in this introduction, Nicoli et al (2020) identify three ideal-types of identification patterns: genuine Europeans, genuine nationals and genuine localists. Genuine Europeans are more supportive of very generous redistributive schemes governed at European level; and the more exclusive is their European identity the more they support these schemes.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
See 4 more Smart Citations
“…The authors assess how collective identities impact on preferences for different designs of EU policy packages (for example, with varying redistribution potential, governance and conditionality). Building on the concepts presented in this introduction, Nicoli et al (2020) identify three ideal-types of identification patterns: genuine Europeans, genuine nationals and genuine localists. Genuine Europeans are more supportive of very generous redistributive schemes governed at European level; and the more exclusive is their European identity the more they support these schemes.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
“…Genuine nationals support certain EU-level social policy packages as long as they entail no long-term redistribution, are less generous and are administered nationally; even more so, the more exclusive is their national attachment. All in all, Nicoli et al (2020) found that rather than driving support for European social policy in general, national and European identities structure support for different types of European social policy: Even individuals with exclusive national identities are ready to support EURS as long as it does not involve cross-country redistribution and as long as the funds are managed by the member states rather than by an EU body.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
See 3 more Smart Citations